Technology of protein fortified functional frozen yoghurt - Mallik, Jarita Mahadeb; Ajay J. Gokhale (Indian Journal of Dairy Science, 2026)
The present study was aimed to fortify protein in frozen yoghurt by incorporating strained yoghurt (chakka). Effect of incorporation of chakka at 12, 16, 20 and 24 per cent (w/w) of ice cream mix base on compositional, physico-chemical properties and microbiological qualities was significant. Incremental level of addition of chakka resulted in significant increase in total solids and protein content, while fat content showed increase and later at higher level of chakka incorporation, showed decrease in fat content compared to control sample. Viscosity of control sample was 224.59 cp that increased significantly (718.42 cp) in sample containing 24% chakka. Similar increasing trend was noted for hardness and melting resistance, while over run decreased by approximately 10 per cent compared to control frozen yoghurt, as level of protein increased (4.12 to 5.73 per cent) in form of chakka at 24 per cent level. Flavour, Body and Texture and Total score was highest in sample containing 20 per cent chakka. Lactic Acid Bacteria count increased as level of chakka increased. Overall 20 per cent addition of chakka was considered best treatment to obtain protein fortified frozen yoghurt.